Fatal Adverse Events Associated With Programmed Cell Death Ligand 1 Inhibitors: A Systematic Review and Meta-Analysis - Wang, Xuewen; Wu, Shijie; Chen, Yaying; Shao, Erqian; Zhuang, Tingting; Lu, Linbin; Chen, Xiong (Frontiers in Pharmacology, 2020)
Purpose: We performed this systematic review and meta-analysis to assess the incidence of fatal adverse events that were associated with the use of programmed cell death ligand 1 (PD-L1) inhibitors, to describe them and to statistically depict factors that were associated with these events. Method: Pubmed, Embase and Cochrane Library were completely searched based on the following terms or relevant Medical Subject Heading ones: “atezolizumab”, “durvalumab”, “avelumab”, and “cemiplimab”. Results: A total of 26 eligible studies were identified, incorporating 6,896 unique participants. The overall incidence was 1.24% (95% CI: 0.93-1.65%). The incidence and odds were higher in patients with non-squamous non-small cell lung cancer (NSCLC) than those with urothelial carcinoma [(2.25 vs. 0.85, p=0.04), (odds ratio [OR]: 2.69; 95% CI: 1.04-6.97, p=0.04)], higher in the middle-aged group than the young group [(1.74 vs. 0.89, p=0.01), (OR: 2.13; 95% CI: 1.26-3.61, p=0.01)], and higher in the trial phase I than the trial phase II [(1.76 vs. 0.60, p=0.01), (OR: 0.31; 95% CI: 0.13-0.75, p=0.01)]. Notably, the trial phase I had a higher incidence than trial phase II or Ⅲ following regulating for cancer types and average age (OR: 0.28; 95% CI: 0.11-0.71, p=0.01, OR: 0.48; 95% CI: 0.24-0.95, p=0.04, respectively). In terms of organ-specific fatal adverse events, interstitial lung disease (ILD) was frequently documented. A variety of respiratory system-related fatal adverse events were recorded, including but not limited to pneumonia and respiratory failure. As for organ-unspecific fatal adverse events, substantial cases of sepsis and neutropenia were recorded. Conclusion: This study firstly provided a comprehensive incidence and the spectrum of fatal adverse events associated with PD-L1 inhibitors, and identified three potential susceptible factors of that, yielding a capability for clinicians to distinguish high-risk populations from relatively low-risk ones, and facilitating to improve the safety of PD-L1 inhibitors broadly used in the clinical setting.